Intraoperative management of patients with incidental catecholamine producing tumors: A literature review and analysis - Stefan Hariskov; Roman Schumann (Wolters Kluwer Medknow Publications, 2013)
Context: Present knowledge about intraoperative management, morbidity, and mortality of patients with undiagnosed catecholamine-producing tumors is mostly based on published case reports and anecdotal evidence. Aims: The aim was to summarize the management and outcomes of reported cases and analyze for practice patterns, deduct useful management recommendations as applicable. Settings and Design: The Medline database was searched with specific keywords for the period of 1988-2010 for cases of incidental pheochromocytomas and paragangliomas. Materials and Methods: Case reports in the English language with a postoperative diagnosis of pheochromocytoma and paraganglioma by histopathology were included. Systematic data extraction from case reports was done. Statistical analysis used: Descriptive statistics were applied. Results: Of 823 retrieved records, 62 case reports met inclusion criteria. Hemodynamic instability occurred primarily during mass manipulation/intraoperatively (52%, n = 32) and induction/laryngoscopy (18%, n = 11). In cases reporting specific antihypertensive treatments, nitrates (67%, n = 30) represented the majority of medications used, followed by beta-blockers (47%, n = 21). Alpha receptor blockers were administered in 33% (n = 15). The perioperative mortality was 8% (n = 5), and none of these patients received intraoperative alpha blockade. A catecholamine-secreting tumor was suspected intraoperatively in 26% of cases. Conclusions: The perioperative mortality based on the reviewed cases of incidental catecholamine producing tumors was less than would traditionally be expected. Intraoperative alpha receptor blockade to treat hypertension was reported in 33% of cases, and none of the patients with a fatal outcome had received it. A higher intraoperative index of suspicion and a lower threshold to consider alpha blocking medications for severe intraoperative hypertension may improve outcomes.